Pulmonary atresia associated with maternal 22q11.2 deletion: possible parent of origin effect in the conotruncal anomaly face syndrome. Issue 11 (November 1994) - Seaver, L H; Pierpont, J W; Erickson, R P; Donnerstein, R L; Cassidy, S B
Abstract : A blind study was designed to test the hypothesis that some persons with a relatively rare cardiac malformation, pulmonary atresia with ventriculoseptal defect (PA/VSD), have a recognisable phenotype. Fourteen patients with cyanotic congenital heart lesions were examined by dysmorphologists blinded to the type of cardiac malformation. Six children were judged to have a similar craniofacial appearance; all had PA/VSD. These children were not originally considered to fall within the classic phenotypes of the DiGeorge sequence or the velocardiofacial syndrome, both of which have been shown to be associated with deletions of 22q11. More recently, 22q11 deletions have been documented in the conotruncal anomaly face syndrome and apparently isolated conotruncal heart defects. A new acronym, CATCH 22 syndrome (Cardiac defects, Abnormal facies, Thymic hypoplasia, Cleft palate, and Hypocalcaemia) has been suggested to encompass this very broad phenotypic spectrum. A preliminary molecular study was conducted using the dinucleotide repeat D22S264 located on chromosome 22q11.2. All cases tested with the subtle but recognisable phenotype had deletions, all lacking the maternal contribution at this locus, suggesting there may be a parent of origin effect.